RETRACTED: Analysis of rotating-symmetric frame and MHD for peristaltic multiphase flow: An exact solution - Fatima, Nahid; Abdulkhaliq M. Alharbi, Khalid; Ijaz, Nouman; Riaz, Arshad; El-Din, ElSayed M. Tag (Frontiers in Physics, 2023)
The rotational mechanism forms the basis of various cosmic and geophysical transports. In medical science, rotational blood flows have been related to healthy cardiac function. This study consists of a mathematical model representing magnetohydrodynamic effects on the two-phase pumping flow of a Ree–Eyring–Powell stress model in a rotating frame. The model is controlled by switching the system into a wave frame of reference for better analysis of the wave phenomenon. Moreover, a lubrication theory is applied to the resulting set of relations in order to get a more comprehensive form of the reduced mathematical model. In the end, an exact solution is found to discuss the substantial contents of the study. The data on velocity and stream function are presented diagrammatically to examine the theoretical behavior of various quantities under the variation of considerable physical factors. It is concluded from the graphs that axial and secondary velocities are decreasing against rotation, magnetic field, and fluid’s factor, but the same rise in the case of wall stiffness and particle concentration. In both industrial and biomedical applications, this type of flow measurement gives tomographic information on the multiphase flow process, which entails acquiring signal changes at the edges of objects like fluid pipes or blood vessels to determine how the objects are distributed within. This work is extendable by considering nanoparticles of various types to enhance the thermal conductivity of the flow.